Exposure to positively- and negatively-charged plasma cluster ions impairs IgE-binding capacity of indoor cat and fungal allergens. Issue 1 (December 2016) - Nishikawa, Kazuo; Fujimura, Takashi; Ota, Yasuhiro; Abe, Takuya; ElRamlawy, Kareem; Nakano, Miyako; Takado, Tomoaki; Uenishi, Akira; Kawazoe, Hidechika; Sekoguchi, Yoshinori; Tanaka, Akihiko; Ono, Kazuhisa; et al.
Abstract Background Environmental control to reduce the amount of allergens in a living place is thought to be important to avoid sensitization to airborne allergens. However, efficacy of environmental control on inactivation of airborne allergens is not fully investigated. We have previously reported that positively- and negatively-charged plasma cluster ions (PC-ions) reduce the IgE-binding capacity of crude allergens from Japanese cedar pollen as important seasonal airborne allergens. Cat (Felis domesticus ) and fungus (Aspergillus fumigatus ) are also important sources of common airborne allergens in living spaces throughout the year, and early sensitization with those allergens is considered to be a risk factor for future development of allergic rhinitis, pollinosis and asthma. The aim of this study is to examine whether the PC-ions reduce the IgE-binding capacity of a cat major allergen (Fel d 1) and fungal allergens in an experimental condition. Methods Fel d 1, crude fungal extract, or a fungal major allergen Asp f 1, was treated with PC-ions for 6 h in an experimental cylindrical apparatus. Sham-treated allergens were prepared in the same experimental apparatus without generation of PC-ions. The degradation of the PC-ions-treated Fel d 1 was analyzed by SDS-PAGE, and the IgE-binding capacity of the PC-ions-treated allergens was analyzed by ELISA inhibition assay. Results Exposure of Fel d 1, crude fungal extract and Asp f 1 to PC-ions significantly decreased protein content of Fel d 1 or Asp f 1, respectively. SDS-PAGE analysis suggested that the decreased Fel d 1 content upon exposure with PC-ions was attributable to protein degradation. ELISA inhibition indicated that the PC-ions treatment significantly impaired IgE-binding capacities of Fel d 1, crude fungal allergens, and Asp f 1 compared to sham treatment. Discussion Our data suggest that treatment with PC-ions not only reduce indoor cat and fungal allergens, but also impair their allergenicity. Conclusion These results suggest that environmental control with PC-ions is useful for inactivation of indoor cat and fungal allergens.